2020
DOI: 10.1039/c9sm01990a
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembling amphiphilic peptide nanoparticle for the efficient entrapment of DNA cargoes up to 100 nucleotides in length

Abstract: To overcome the low efficiency and cytotoxicity associated with most non-viral DNA delivery systems we developed a purely peptidic self-assembling system that is able to entrap single- and double-stranded DNA of up to 100 nucleotides in length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…We have demonstrated that KIW7 is able to promote cell surface association and partially deliver DNA with ~200 bp into HeLa cells, indicating the potential of this truncated version of Penetratin for the transport of nucleotide sequences larger than those successfully transported by CPPs in recent reports. 67,68 In fact, 200bp DNA duplexes internalized with assistance of KIW7 are about 10 times larger than microRNA and siRNA used to regulate cell metabolism and therefore KIW7 is potentially suitable for delivery of these species or even oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that KIW7 is able to promote cell surface association and partially deliver DNA with ~200 bp into HeLa cells, indicating the potential of this truncated version of Penetratin for the transport of nucleotide sequences larger than those successfully transported by CPPs in recent reports. 67,68 In fact, 200bp DNA duplexes internalized with assistance of KIW7 are about 10 times larger than microRNA and siRNA used to regulate cell metabolism and therefore KIW7 is potentially suitable for delivery of these species or even oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane active peptides interact with cellular membranes by traversing them, disrupting them or by residing at the membrane interface and fusing with them [19]. They are known to overcome site-specific delivery barriers and facilitate intracellular delivery of various bioactive cargos with low cytotoxicity [19,20]. Although there is a wide variety of membrane-active peptides, here we mainly discuss peptides for targeting nucleic acid delivery systems to specific cells and tissues, and peptides that assist in the delivery of nanocarriers across membrane barriers, such as cell penetrating peptides (CPPs), peptides facilitating endosomal escape and those that target nanocarriers to subcellular organelles (Figure 1).…”
Section: Peptide-guided Delivery Of Nucleic Acids Across Biological Barriersmentioning
confidence: 99%
“…The peptide-based micelles were non-cytotoxic at various concentrations and demonstrated superior delivery efficiency over common transfection agents, like Lipofectamine 2000 or Lipofectin ® . In another example, a rationally designed amphiphilic peptide that self-assembled into multicompartment micelles (MCMs) was able to efficiently entrap single- and double-stranded DNA up to 100 nucleotides in length ( Figure 2 A,B) [ 40 ]. These purely peptidic, nanosized MCMs demonstrated rapid and efficient uptake by cells ( Figure 2 C).…”
Section: Peptide-based Supramolecular Nanoassembliesmentioning
confidence: 99%
“…( B ) Normalized fluorescence correlation spectroscopy (FCS) autocorrelation curves for fluorescently labelled 100 nt ssDNA and 100 bp dsDNA (free and loaded in multi-compartment micelles). ( C ) Confocal laser scanning microscopy (CLSM) merged images (GFP and Atto550) of H2B-GFP expressing HeLa cells treated with 100 nt/bp ss/dsDNA-loaded (HR)3gT multi-compartment micelle nanoparticles after 24 h. Adapted and modified from [ 40 ], with permission. Copyright: 2020 Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%